Hypomorphic FANCA mutations correlate with mild mitochondrial and clinical phenotype in Fanconi anemia. - Bottega, Roberta; Nicchia, Elena; Cappelli, Enrico; Ravera, Silvia; De Rocco, Daniela; Faleschini, Michela; Corsolini, Fabio; Pierri, Filomena; Calvillo, Michaela; Russo, Giovanna; Casazza, Gabriella; Ramenghi, Ugo; et al. (Haematologica, 2018)
Fanconi anemia is a rare disease characterized by congenital malformations, aplastic anemia, and predisposition to cancer. Despite the consolidated role of the Fanconi anemia proteins in DNA repair, their involvement in mitochondrial function is emerging. The purpose of this work was to assess whether the mitochondrial phenotype, independent of genomic integrity, could correlate with patient phenotype. We evaluated mitochondrial and clinical features of 11 affected individuals homozygous or compound heterozygous for p.His913Pro and p.Arg951Gln/Trp, the two residues of FANCA that are more frequently affected in our cohort of patients. Although p.His913Pro and p.Arg951Gln proteins are stably expressed in cytoplasm, they are unable to migrate in the nucleus, preventing cells from repairing DNA. In these cells, the electron transfer between respiring complex I-III is reduced and the ATP/AMP ratio is impaired with defective ATP production and AMP accumulation. These activities are intermediate between those observed in wild-type and FANCA-/- cells, suggesting that the variants at residues His913 and Arg951 are hypomorphic mutations. Consistent with these findings, the clinical phenotype of most of the patients carrying these mutations is mild. These data further support the recent finding that the Fanconi anemia proteins play a role in mitochondria, and open up possibilities for genotype/phenotype studies based on novel mitochondrial criteria.

Defects in mitochondrial energetic function compels Fanconi Anaemia cells to glycolytic metabolism. - Cappelli, Enrico; Cuccarolo, Paola; Stroppiana, Giorgia; Miano, Maurizio; Bottega, Roberta; Cossu, Vanessa; Degan, Paolo; Ravera, Silvia (Biochim Biophys Acta Mol Basis Dis, 2017)
Energetic metabolism plays an essential role in the differentiation of haematopoietic stem cells (HSC). In Fanconi Anaemia (FA), DNA damage is accumulated during HSC differentiation, an event that is likely associated with bone marrow failure (BMF). One of the sources of the DNA damage is altered mitochondrial metabolism and an associated increment of oxidative stress. Recently, altered mitochondrial morphology and a deficit in the energetic activity in FA cells have been reported. Considering that mitochondria are the principal site of aerobic ATP production, we investigated FA metabolism in order to understand what pathways are able to compensate for this energy deficiency. In this work, we report that the impairment in mitochondrial oxidative phosphorylation (OXPHOS) in FA cells is countered by an increase in glycolytic flux. By contrast, glutaminolysis appears lower with respect to controls. Therefore, it is possible to conclude that in FA cells glycolysis represents the main pathway for producing energy, balancing the NADH/NAD ratio by the conversion of pyruvate to lactate. Finally, we show that a forced switch from glycolytic to OXPHOS metabolism increases FA cell oxidative stress. This could be the cause of the impoverishment in bone marrow HSC during exit from the homeostatic quiescent state. This is the first work that systematically explores FA energy metabolism, highlighting its flaws, and discusses the possible relationships between these defects and BMF.
Keywords: Cell Line; Fanconi Anemia; Glycolysis; Humans; Mitochondria; Oxidative Phosphorylation; Oxidative Stress

Evaluation of energy metabolism and calcium homeostasis in cells affected by Shwachman-Diamond syndrome. - Ravera, Silvia; Dufour, Carlo; Cesaro, Simone; Bottega, Roberta; Faleschini, Michela; Cuccarolo, Paola; Corsolini, Fabio; Usai, Cesare; Columbaro, Marta; Cipolli, Marco; Savoia, Anna; Degan, Paolo; et al. (Sci Rep, 2016)
Isomorphic mutation of the SBDS gene causes Shwachman-Diamond syndrome (SDS). SDS is a rare genetic bone marrow failure and cancer predisposition syndrome. SDS cells have ribosome biogenesis and their protein synthesis altered, which are two high-energy consuming cellular processes. The reported changes in reactive oxygen species production, endoplasmic reticulum stress response and reduced mitochondrial functionality suggest an energy production defect in SDS cells. In our work, we have demonstrated that SDS cells display a Complex IV activity impairment, which causes an oxidative phosphorylation metabolism defect, with a consequent decrease in ATP production. These data were confirmed by an increased glycolytic rate, which compensated for the energetic stress. Moreover, the signalling pathways involved in glycolysis activation also appeared more activated; i.e. we reported AMP-activated protein kinase hyper-phosphorylation. Notably, we also observed an increase in a mammalian target of rapamycin phosphorylation and high intracellular calcium concentration levels ([Ca(2+)]i), which probably represent new biochemical equilibrium modulation in SDS cells. Finally, the SDS cell response to leucine (Leu) was investigated, suggesting its possible use as a therapeutic adjuvant to be tested in clinical trials.

Somatic, hematologic phenotype, long-term outcome, and effect of hematopoietic stem cell transplantation. An analysis of 97 Fanconi anemia patients from the Italian national database on behalf of the Marrow Failure Study Group of the AIEOP (Italian Associ - Svahn, Johanna; Bagnasco, Francesca; Cappelli, Enrico; Onofrillo, Daniela; Caruso, Silvia; Corsolini, Fabio; De Rocco, Daniela; Savoia, Anna; Longoni, Daniela; Pillon, Marta; Marra, Nicoletta; Ramenghi, Ugo; et al. (Am J Hematol, 2016)
We analyzed 97 Fanconi anemia patients from a clinic/biological database for genotype, somatic, and hematologic phenotype, adverse hematological events, solid tumors, and treatment. Seventy-two patients belonged to complementation group A. Eighty percent of patients presented with mild/moderate somatic phenotype and most with cytopenia. No correlation was seen between somatic/hematologic phenotype and number of missense mutations of FANCA alleles. Over follow-up, 33% of patients improved or maintained mild/moderate cytopenia or normal blood count, whereas remaining worsened cytopenia. Eleven patients developed a hematological adverse event (MDS, AML, pathological cytogenetics) and three developed solid tumors. 10 years cumulative risk of death of the whole cohort was 25.6% with median follow-up 5.8 years. In patients eligible to hematopoietic stem cell transplantation because of moderate cytopenia, mortality was significantly higher in subjects transplanted from matched unrelated donor over nontransplanted subjects, whereas there was no significant difference between matched sibling donor transplants and nontransplanted patients. In patients eligible to transplant because of severe cytopenia and clonal disease, mortality risk was not significantly different in transplanted from matched unrelated versus matched sibling donor versus nontransplanted subjects. The decision to transplant should rely on various elements including, type of donor, HLA matching, patient comorbidities, impairment, and clonal evolution of hematopoiesis. Am. J. Hematol. 91:666-671, 2016. © 2016 Wiley Periodicals, Inc.

Clinical aspects of Fanconi anemia individuals with the same mutation of FANCF identified by next generation sequencing. - Nicchia, Elena; Benedicenti, Francesco; Rocco, Daniela De; Greco, Chiara; Bottega, Roberta; Inzana, Francesca; Faleschini, Michela; Bonin, Serena; Cappelli, Enrico; Mogni, Massimo; Stanzial, Franco; Svahn, Johanna; et al. (Birth Defects Res A Clin Mol Teratol, 2015)
BACKGROUND: Fanconi anemia (FA) is a rare genetic disease characterized by congenital malformations, aplastic anemia and increased risk of developing malignancies. FA is genetically heterogeneous as it is caused by at least 17 different genes. Among these, FANCA, FANCC, and FANCG account for approximately 85% of the patients whereas the remaining genes are mutated in only a small percentage of cases. For this reason, the molecular diagnostic process is complex and not always extended to all the FA genes, preventing the characterization of individuals belonging to rare groups. METHODS: The FA genes were analyzed using a next generation sequencing approach in two unrelated families. RESULTS: The analysis identified the same, c.484_485del, homozygous mutation of FANCF in both families. A careful examination of three electively aborted fetuses in one family and one affected girl in the other indicated an association of the FANCF loss-of-function mutation with a severe phenotype characterized by multiple malformations. CONCLUSION: The systematic use of next generation sequencing will allow the recognition of individuals from rare complementation groups, a better definition of their clinical phenotypes, and consequently, an appropriate genetic counseling. Birth Defects Research (Part A) 103:1003-1010, 2015. © 2015 Wiley Periodicals, Inc.

Impaired immune response to Candida albicans in cells from Fanconi anemia patients. - Parodi, Alessia; Kalli, Francesca; Svahn, Johanna; Stroppiana, Giorgia; De Rocco, Daniela; Terranova, Paola; Dufour, Carlo; Fenoglio, Daniela; Cappelli, Enrico (Cytokine, 2015)
Fanconi anemia (FA) is a genetic disorder characterized by bone marrow failure and cancer predisposition. Several studies show alterations of the immunological status of FA patients including defects in peripheral blood lymphocyte subsets, serum immunoglobulin levels, and inflammatory cytokines. However scanty information is available on the response of FA cells to specific infectious antigens. In this work we examined the response of FA cells to different immunological stimuli and found a defective response of IL-1β, TNF-α and IL-17 to Candida albicans stimulation thus pointing to a potentially impaired response to fungal infections of FA patients.
Keywords: Adolescent; Candida albicans; CD8-Positive T-Lymphocytes; Cell Proliferation; Cells, Cultured; Child; Child, Preschool; Cytokines; Fanconi Anemia; Humans; Immunity; Infant; Young Adult

Molecular analysis of Fanconi anemia: the experience of the Bone Marrow Failure Study Group of the Italian Association of Pediatric Onco-Hematology. - De Rocco, Daniela; Bottega, Roberta; Cappelli, Enrico; Cavani, Simona; Criscuolo, Maria; Nicchia, Elena; Corsolini, Fabio; Greco, Chiara; Borriello, Adriana; Svahn, Johanna; Pillon, Marta; Mecucci, Cristina; et al. (Haematologica, 2014)
Fanconi anemia is an inherited disease characterized by congenital malformations, pancytopenia, cancer predisposition, and sensitivity to cross-linking agents. The molecular diagnosis of Fanconi anemia is relatively complex for several aspects including genetic heterogeneity with mutations in at least 16 different genes. In this paper, we report the mutations identified in 100 unrelated probands enrolled into the National Network of the Italian Association of Pediatric Hematoly and Oncology. In approximately half of these cases, mutational screening was carried out after retroviral complementation analyses or protein analysis. In the other half, the analysis was performed on the most frequently mutated genes or using a next generation sequencing approach. We identified 108 distinct variants of the FANCA, FANCG, FANCC, FANCD2, and FANCB genes in 85, 9, 3, 2, and 1 families, respectively. Despite the relatively high number of private mutations, 45 of which are novel Fanconi anemia alleles, 26% of the FANCA alleles are due to 5 distinct mutations. Most of the mutations are large genomic deletions and nonsense or frameshift mutations, although we identified a series of missense mutations, whose pathogenetic role was not always certain. The molecular diagnosis of Fanconi anemia is still a tiered procedure that requires identifying candidate genes to avoid useless sequencing. Introduction of next generation sequencing strategies will greatly improve the diagnostic process, allowing a rapid analysis of all the genes.
Keywords: Amino Acid Substitution; Cell Line; Cohort Studies; Computational Biology; Databases, Nucleic Acid; Fanconi Anemia; Fanconi Anemia Complementation Group Proteins; Founder Effect; Genotype; Humans; Italy; Mosaicism; Mutation; Polymorphism, Single Nucleotide

Unusual splice site mutations disrupt FANCA exon 8 definition. - Mattioli, Chiara; Pianigiani, Giulia; De Rocco, Daniela; Bianco, Anna Monica Rosaria; Cappelli, Enrico; Savoia, Anna; Pagani, Franco (Biochim Biophys Acta, 2014)
The pathological role of mutations that affect not conserved splicing regulatory sequences can be difficult to determine. In a patient with Fanconi anemia, we identified two unpredictable splicing mutations that act on either sides of FANCA exon 8. In patients-derived cells and in minigene splicing assay, we showed that both an apparently benign intronic c.710-5T>C transition and the nonsense c.790C>T substitution induce almost complete exon 8 skipping. Site-directed mutagenesis experiments indicated that the c.710-5T>C transition affects a polypyrimidine tract where most of the thymidines cannot be compensated by cytidines. The c.790C>T mutation located in position -3 relative to the donor site induce exon 8 skipping in an NMD-independent manner and complementation experiments with modified U1 snRNAs showed that U1 snRNP is only partially involved in the splicing defect. Our results highlight the importance of performing splicing functional assay for correct identification of disease-causing mechanism of genomic variants and provide mechanistic insights on how these two FANCA mutations affect exon 8 definition.
Keywords: Base Sequence; Cell Line, Tumor; Codon, Nonsense; Exons; Fanconi Anemia Complementation Group A Protein; HeLa Cells; Humans; Introns; Molecular Sequence Data; Mutagenesis, Site-Directed; Ribonucleoproteins, Small Nuclear; RNA Splice Sites; RNA Splicing